Pengaruh Intellectual Capital terhadap Kinerja Perbankan dengan Sustainable Growth Rate sebagai Variabel Intervening - Teguh Erawati; Suyanto; Maghfirotus Shafira (Yayasan Literasi Ilmiah Indonesia, 2026)
Purpose: This study aims to analyze the effect of human capital, capital employed, and structural capital on banking performance, with the sustainable growth rate as an intervening variable in banks in Indonesia listed on the Indonesia Stock Exchange. Method: This study uses a quantitative approach with panel data regression analysis as the analytical tool. The research population consist of all This study uses a quantitative approach with panel data regression analysis as the analytical tool. The research population consists of all conventional commercial banks listed on the Indonesia Stock Exchange during the 2020–2024 period. The research sample was determined using documentating, resulting in 29 banks that met the data completeness criteria. Thus, 145 data points were obtained. Data processing was carried out using EViews 12. Finding: This study found that intellectual capital, proxied through human capital efficiency, structural capital efficiency, and capital employed efficiency, plays an important role in driving the sustainable growth rate of banks. Furthermore, the sustainable growth rate is proven to affect banking performance, measured using Return on Assets (ROA). These findings indicate that sustainable growth acts as a linking mechanism between the management of intellectual assets and the improvement of banks' financial performance. Novelty: The novelty of this research lies in the use of the sustainable growth rate as an intervening variable in explaining the mechanism of the impact of intellectual capital on banking performance. This study provides empirical evidence based on panel data of Indonesian banks for the 2020–2024 period, which is still relatively limited in previous literature.